Optimasi Model Pengiriman Bantuan Bencana Gempa Bumi di BPBD Kabupaten Bantul - Yohanes Anton Nugroho (Universitas Ahmad Dahlan Indonesia, 2019)
Bantul regency had experienced of the disasters caused by the earthquake occurred in Bantul in 2006, where 4121 residents of Bantul region was died, thousands buildings was collapsed and many damage many places.Â This paper develop a model of earthquake demage and analyzes distributing humanitarian aid from BPBD Bantul to each warehouse distributor in each districts that classified as Vehicle Routing Problem With Time Window (VRPTW). This solution model is developed using Linear Programming and The Nearest Neighbors Algorithm s Algorithm. Goal of those methods are expected to get distribution solution more fast and efficient. Based on modeling result using scenario of refugee number 80% from population in very vulnerable area, 60% in vulnerable area, and 40% in less vulnerable area obtained mathematical model of allocation distribution done by optimization with Linear Programming, which obtained distribution allocation solution using 16 medium trucks and 4 heavy trucks only need 3 days.